Hate, humor and bystander reactions: Danish adolescent reactions to hateful political memes - Lindekilde, Lasse; Rasmussen, Jesper (Politica, 2022)
Most people recognize hateful content that is followed by a swastika or an IS flag. However, hateful content is often embedded in seemingly innocent humorous memes making it harder for bystanders to recognize and decode. In this article, we examine how Danish adolescents assess hateful memes and how these assessments shape their intention to intervene pro-socially by reporting hateful content and anti-socially by sharing and liking hateful content. Furthermore, the article tests predictors of pro-social and anti-social reactions to hateful content on social media across gender, political interest, as well as legal and violent political activism intentions. The article draws on an electronic survey among 814 Danish primary and secondary school students.